Analyse perceptuelle de l’assurance-vie auprès des gradués universitaires - Outreville, J.-François; Pallaver, J.-Jacques; Zins, Michel (Assurances)

(untitled) (HEC Montréal, 1984)
A research team set up by the Chaire en Assurance of Laval University has produced a paper on an unusual subject. With the permission of those concerned, here is the text with its conclusions: "Word of mouth publicity seems still to be the best way to convince someone to take out life insurance. However, the professional competence and training of salesmen are essential, not only because it is the salesmen who are the ultimate influence on a decision, but more especially because a satisfied client is a fine advertisement. The effect of formal advertising is still very limited. Possibly it is badly directed and, rather than mention the risk of disease or accident, stress should be put on the professional training of the agents and the importance of financial planning".